Detection of Brucella spp. from milk by quantitative PCR as a monitoring method for brucellosis in cattle in Mongolia - Batsukh Naranchimeg; Batsaikhan Chantsal; Badrakh Sandagdorj; Tsognemekh Bolormaa; Purevdorj Ulzii-Orshikh; Adilbish Altanchimeg; Sumiya Ganzorig; Vanaabaatar Batbaatar; Motohiro Horiuchi; Purevdorj Nyam-Osor (BMC Veterinary Research)
Abstract Background Brucellosis in livestock is endemic in Mongolia, and efficient monitoring is required for clarifying its prevalence. Milk can be obtained noninvasively and is useful for monitoring brucellosis in livestock. However, the usefulness of milk in monitoring brucellosis should be clarified. Materials and methods Serum and milk samples were obtained from 326 cows from six farms near Ulaanbaatar City between 2020 and 2022. Serum and milk were assessed using the Rose Bengal Test (RBT) and Milk Ring Test (MRT), respectively. All milk samples were further subjected to bacterial isolation and DNA extraction. DNA samples were analyzed with quantitative PCR (qPCR) targeting Brucella genus-specific IS711 insertion sequence to detect and estimate Brucella spp. levels in milk. qPCR-positive samples were further subjected to single nucleotide polymorphism (SNP) assay to discriminate B. abortus field strains from the S19 vaccine strain. Results Of the 326 milk samples, 108 (33.1%) were revealed to be positive for Brucella spp. by qPCR, whereas only 5 samples (1.5%) were deemed positive via the bacterial isolation. No S19 vaccine strain was identified in the IS711 qPCR-positive milk samples by the SNP assay. Although qPCR detected Brucella spp. from milk, which was obtained from cows in three lactation stages, the detection ratio was significantly higher in the early lactation stage than in the middle lactation stage. Additionally, the five milk samples from which Brucella spp, were isolated exhibited the top 5 estimated colony forming units among the IS711 qPCR-positive samples, indicating that detection sensitivity of the IS711 qPCR is extremely higher than that of bacterial culture. There was a tendency that milk samples from RBT- and MRT-positive cows are more likely to be positive by IS711 qPCR. Conclusion The results revealed that analysis of milk with qPCR is easy and sensitive monitoring method for detecting Brucella infection in livestock.